Behind the Scenes of Instagram: The Relationship Between Self-Esteem and Narcissistic Tendencies Among Gen Z - Harod, Yabes Mahanaim; Goretti Adiyanti, Maria (Psikoborneo: Jurnal Ilmiah Psikologi, 2025)
The phenomenon of Gen Z's existence is beginning to increase on social media, potentially giving rise to narcissistic tendencies, especially about the level of self-esteem that individuals have. This study aims to analyze the relationship between self-esteem and narcissistic tendencies in Gen Z on Instagram social media. The study used a quantitative approach with a correlational design, with a purposive sampling technique involving 148 Gen Z participants who actively use Instagram social media. Data collection was conducted using the Coopersmith Self-Esteem Inventory (CSEI) and the Narcissism on Social Media Scale (NSMS). The results of data analysis using Spearman correlation, showed a significant negative relationship between self-esteem and narcissistic tendencies (r = -0.645, p < 0.05). The lower the self-esteem, the higher the narcissistic tendencies on Instagram social media, and vice versa. The findings reinforce the view that narcissistic tendencies are often used as a compensation mechanism for low self-esteem. This study provides practical implications to help Gen Z understand the importance of improving self-esteem to prevent maladaptive narcissistic tendencies on social media.Fenomena eksistensi Gen Z mulai meningkat di media sosial, berpotensi memunculkan kecenderungan narsistik, terutama berkaitan dengan tingkat self-esteem yang dimiliki individu. Penelitian ini bertujuan untuk menganalisis hubungan antara self-esteem dengan kecenderungan narsistik pada Gen Z di media sosial Instagram. Penelitian menggunakan pendekatan kuantitatif dengan desain korelasional, dengan teknik purposive sampling yang melibatkan 148 partisipan Gen Z yang aktif menggunakan media sosial Instagram. Pengumpulan data dilakukan menggunakan Coopersmith Self-Esteem Inventory (CSEI) dan Narcissism on Social Media Scale (NSMS). Hasil analisis data menggunakan korelasi Spearman, menunjukkan adanya hubungan negatif yang signifikan antara self-esteem dan kecenderungan narsistik (r = -0,645, p < 0,05). Semakin rendah self-esteem, semakin tinggi kecenderungan narsistik di media sosial Instagram, dan sebaliknya. Temuan memperkuat pandangan bahwa kecenderungan narsistik sering dijadikan mekanisme kompensasi atas self-esteem yang rendah. Penelitian ini memberikan implikasi praktis yang dapat membantu Gen Z dalam memahami pentingnya meningkatkan self-esteem untuk mencegah kecenderungan narsistik yang maladaptif di media sosial.